Management of Ankyloglossia: Comparison of Pre-Suturing Scalpel Technique, Electrosurgery and Dlode Laser Methods - Pradhan, Ameena (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To compare various novel surgical techniques for management of Kotlow’s Class III and IV ankyloglossia,in terms of intra-operative bleeding, postoperative pain and satisfaction of the patients. Material and Methods: Patients older than the age of 15 years, with ankyloglossia ready for the surgical procedure were enrolled in the study. All Ankyloglossia was managed by a frenectomy procedure using a pre-suturing scalpel method (group A); frenectomy procedure using electrocautry (groupB) or frenectomy with Diode laser without suture (group C) from January 2012 to June 2014. These three techniques were compared in order to assess intra-operative bleeding, postoperative pain and satisfaction of the patients towards these techniques. Results: Total of 16 patients with ankyloglossia was operated during the study period. Out of sixteen, seven patients were in group A, five in group B and four in group C. There was no significant bleeding during surgery in all the cases. Post- operative visual analog scale (VAS) was highest in group B at 24 and 48 hours during speaking. (Mean VAS= 6.4 with S.D.0.82 and 6.0 with S.D 0.7). Patients’ satisfaction was higher towards laser. Conclusion: For management of ankyloglossia,a frenectomy procedure using a pre-suturing scalpel method; frenectomy procedure using electrocautry or frenectomy with Diode laser without suture can be performed safely without significant bleeding with minimal pain and greater patients’ satisfaction. Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, page: 11-14